Agricultural Mothers’ Conversations & Decision-Making about Food - Alyssa Rockers; Quisto Settle; Dwayne Cartmell (Journal of Applied Communications, 2020)
Agricultural organizations have encouraged farmers and others involved in the agricultural industry to discuss their experiences with consumers and to have meaningful conversations about food. While agriculturalists are encouraged to share their stories on the internet through social networking platforms and blogs, they are also encouraged to have interpersonal conversations about food and agriculture. Due to the elevated concerns of mothers about food and the nature of women and social capital, we need to understand how mothers communicate about food. This qualitative study utilized in-depth interviews with mothers with agricultural backgrounds to answer two research questions: 1) How are mothers sharing and receiving information about food? 2) How does information they receive affect mothers’ food purchasing decisions? Using constant comparative method, participants’ responses were organized into themes. The themes that emerged were information sharing is often limited to certain scenarios, information receiving is mainly online, concerns about food are common, strangers are easiest to talk to about food and agriculture issues, and social pressures exist but are not felt by all. While some mothers were willing to discuss food and agricultural issues with others, many participants were hesitant to discuss them to avoid tensions with acquaintances and those they were close to. As a result of their hesitance, mothers are not having the conversations encouraged by agricultural organizations. Some mothers feel judgment from their peers in the form of social pressure while grocery shopping, which indicates peer relationships can influence food purchasing.
Keywords: mothers; food; conversations; feminist standpoint theory